Evaluation of Phytochemical Constituents and Antimicrobial Activity of Calotropis procera Root Extract against some Pathogenic Microorganisms in Yola, Adamawa State, Nigeria - Shitu, A. S.; Salisu, Z. N.; Johnson, A. A. (UMYU Journal of Microbiology Research)
Study’s Novelty/Excerpt